Design, Synthesis and Biological Activity Evaluation of S-Substituted 1H-5-Mercapto-1,2,4-Triazole Derivatives as Antiproliferative Agents in Colorectal Cancer - Mioc, Marius; Avram, Sorin; Bercean, Vasile; Kurunczi, Ludovic; Ghiulai, Roxana M.; Oprean, Camelia; Coricovac, Dorina E.; Dehelean, Cristina; Mioc, Alexandra; Balan-Porcarasu, Mihaela; Tatu, Calin; Soica, Codruta (Frontiers in Chemistry, 2018)
Colon cancer is a widespread pathology with complex biochemical etiology based on a significant number of intracellular signaling pathways that play important roles in carcinogenesis, tumor proliferation and metastasis. These pathways function due to the action of key enzymes that can be used as targets for new anticancer drug development. Herein we report the synthesis and biological antiproliferative evaluation of a series of novel S-substituted 1H-3-R-5-mercapto-1,2,4-triazoles, on a colorectal cancer cell line, HT-29. Synthesized compounds were designed by docking based virtual screening (DBVS) of a previous constructed compound library against protein targets, known for their important role in colorectal cancer signaling: MEK1, ERK2, PDK1, VEGFR2. Among all synthesized structures, TZ55.7, which was retained as a possible PDK1 (phospholipid-dependent kinase 1) inhibitor, exhibited the most significant cytotoxic activity against HT-29 tumor cell line. The same compound alongside other two, TZ53.7 and TZ3a.7, led to a significant cell cycle arrest in both sub G0/G1 and G0/G1 phase. This study provides future perspectives for the development of new agents containing the 1,2,4-mercapto triazole scaffold with antiproliferative activities in colorectal cancer.